Electrolyte and battery

CN123018140APending Publication Date: 2026-10-30HIGHPOWER TECH HUIZHOU +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611178926.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]针对现有电解液在高能量密度条件下热稳定性不足、界面调控能力有限,且热安全技术难以实现对热失控全过程的精准、分级、主动防护,往往导致电池安全性与电化学性能难以兼顾的问题,本发明提供了一种电解液及电池

Benefits of technology

[0018]根据本发明提供的电解液,通过精确调控热触发原位聚合添加剂中可聚合单体(M%)与热引发剂(I%)的含量及其比值(M/I),可以仅在异常升温时触聚合反应,常温下稳定,不影响电池正常循环性能;而且,在热失控初期快速形成致密、连续、高覆盖性的聚合物隔离膜,有效切断正负极间放热链式反应;另外,在保障高安全性的前提下,维持电解液良好的离子电导率与电极/电解质界面稳定性,避免因添加剂过量导致的倍率性能衰减;同时,添加剂可直接溶于商用碳酸酯电解液,无需改变现有电池制造流程。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides an electrolyte and a battery, comprising a thermal trigger in-situ polymerization additive, the thermal trigger in-situ polymerization additive comprising a polymerizable monomer additive and a thermal initiator; the percentage of the polymerizable monomer additive in the total mass of the electrolyte is M%, the value range of M being 0.4-5; the percentage of the thermal initiator in the total mass of the electrolyte is I%, the value range of I being 0.5-2; the value of M and the value of I satisfy the following condition: formula 1: 0.2<=M / I<=5.0. By accurately controlling the content and ratio of the polymerizable monomer and the thermal initiator in the thermal trigger in-situ polymerization additive, the application can trigger the polymerization reaction only when the temperature abnormally rises, is stable at normal temperature and does not affect the normal cycle performance of the battery; and a dense, continuous and high-coverage polymer isolation film is quickly formed in the initial stage of thermal runaway, thereby effectively cutting off the heat release chain reaction between the positive and negative electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically to an electrolyte and a battery. Background Technology

[0002] As consumer electronics devices continue to evolve towards thinner and lighter designs and longer battery life, and as new energy vehicles pursue maximum range (mainstream models have moved from 300 km to over 600 km) and fast charging performance, the energy density, specific capacity, and operating voltage of lithium-ion batteries are constantly being increased. However, the improvement in energy density often comes at the cost of sacrificing the thermodynamic stability of the system. The core components of current commercial lithium-ion batteries—highly oxidizing layered cathode materials (such as NCM / NCA), highly reducing anode materials (such as graphite and silicon-based composite materials), and flammable carbonate-based organic electrolytes—are essentially in a thermodynamically metastable state. Under high voltage and highly active electrode conditions, the chemical and electrochemical stability of the electrode / electrolyte interface decreases significantly, easily inducing the decomposition of the solid electrolyte interphase (SEI) and cathode electrolyte interphase (CEI), and triggering a series of exothermic side reactions.

[0003] Under extreme conditions such as mechanical shock, overcharging, over-discharging, or thermal abuse, the internal temperature of the battery rises rapidly, initiating a self-accelerating chain reaction of "initial heat release → violent heat generation → explosive heat release," ultimately leading to thermal runaway and serious safety accidents such as fires and explosions. This safety bottleneck has become a key obstacle restricting the further commercialization and large-scale application of high-energy-density lithium-ion batteries. Therefore, developing novel electrolyte systems that combine high oxidation stability, excellent interface control capabilities, and active thermal response characteristics has become a core technological path to achieve a synergistic improvement in high energy density and high safety.

[0004] Currently, mainstream thermal safety enhancement strategies in the industry generally suffer from problems such as incomplete coverage, delayed response, or performance degradation, making it difficult to effectively intervene in the entire process of thermal runaway. Traditional flame retardant additives (such as organophosphorus compounds and fluorocarbonates): Although they can inhibit electrolyte combustion through free radical capture mechanisms, they usually have high viscosity or electrochemical inertness, which significantly degrades the battery's room temperature cycle performance (capacity retention rate decreases by 10%–20%) and rate performance. Moreover, they only act on the combustion stage at the end of thermal runaway and have almost no inhibitory effect on the key exothermic processes in the early stage (such as SEI decomposition and negative electrode-electrolyte reaction). Physical protection technologies (such as PTC elements and thermal shutdown separators) rely on resistance changes or pore closure to cut off the current. They can only terminate external triggering at the circuit level and cannot suppress the chemical exothermic reaction that has already started inside the battery, making it difficult to block the self-sustaining evolution of thermal runaway. Traditional film-forming additives (such as VC and FEC) can build an SEI film in the first cycle and improve the stability of room temperature cycling, but the film layer formed has poor thermal stability (it begins to decompose at >90℃) and does not have the ability to dynamically repair or continuously protect at high temperatures, and cannot cope with the severe interfacial side reactions in the medium and high temperature range. Single-threshold thermal response additives (such as benzoxazine and melamine derivatives) only trigger polymerization to form a barrier at a specific high temperature (usually >180℃), while thermal runaway is a multi-stage progressive process from low temperature (~90℃) to high temperature (>250℃). A single response point has a significant temperature blind zone, making it difficult to achieve full-cycle protection. In-situ gel electrolyte solution: Its gelation mostly relies on electrochemical or photo-initiated mechanisms, which are weakly correlated with temperature signals. It lacks the ability to sense and grade the critical temperature nodes of thermal runaway, and the timing and effectiveness of protection are difficult to accurately match the actual thermal evolution path.

[0005] In summary, existing technologies are either limited to a single protection mechanism, or their response temperature is disconnected from the thermal runaway process, or they sacrifice electrochemical performance. They are currently unable to achieve proactive intervention across the entire thermal runaway chain, multiple stages, and precise grading. Therefore, there is an urgent need to develop a novel electrolyte design strategy that can intelligently respond according to temperature gradients, actively construct stable interfaces at key exothermic nodes, and simultaneously consider both electrochemical performance and intrinsic safety, in order to overcome the safety bottleneck of high-energy-density lithium-ion batteries. Summary of the Invention

[0006] To address the problems of insufficient thermal stability and limited interface control capabilities of existing electrolytes under high energy density conditions, and the difficulty in achieving precise, graded, and active protection against the entire thermal runaway process through thermal safety technologies, which often leads to a trade-off between battery safety and electrochemical performance, this invention provides an electrolyte and a battery.

[0007] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: This invention provides an electrolyte comprising a thermally triggered in-situ polymerization additive, wherein the thermally triggered in-situ polymerization additive comprises a polymerizable monomer additive and a thermal initiator; taking the total mass of the electrolyte as 100%, the percentage content of the polymerizable monomer additive in the total mass of the electrolyte is M%, where M ranges from 0.4 to 5; the percentage content of the thermal initiator in the total mass of the electrolyte is 1%, where 1 ranges from 0.5 to 2; the values ​​of M and 1 satisfy the following conditions: Equation 1: 0.2≤M / I≤5.0.

[0008] Optionally, the thermally triggered in-situ polymerization additive further includes a polymerization inhibitor, wherein the polymerization inhibitor accounts for R% of the total mass of the electrolyte, and the value of R ranges from 0.005 to 0.1; the M value, the I value, and the R value satisfy the following conditions: Equation 2: 10≤(M+I) / R≤500.

[0009] Optionally, the value of M ranges from 1 to 4; the value of I ranges from 1 to 2; the value of R ranges from 0.01 to 0.05; and the values ​​of M, I, and R satisfy the following conditions: Equation 3: 0.5 ≤ M / I ≤ 2.0; Equation 4: 40≤(M+I) / R≤200.

[0010] Optionally, the polymerizable monomer additive includes a C=C functional group and a functional side chain; the C=C functional group includes one or more of CH2=C(R)-COO-, CH2=CH-, CH2=CH-CH2-, or -C≡CH; the functional side chain includes -C n H 2n-1 (1≤n≤6), -O-, -F, -C n F 2n-1 (1≤n≤6), -OC n H 2n - (1≤n≤6), one or more of cyclic carbonates and -CN.

[0011] Optionally, the polymerizable monomer additive includes One or more of the following: trifluoroethyl methacrylate, 1,3-dioxolane-2-one vinyl ether, allyl glycidyl ether, perfluorohexyl ethyl acrylate, and 2-vinyl-1,3-dioxolane.

[0012] Optionally, the thermal initiator includes at least two of a first thermal initiator, a second thermal initiator, and a third thermal initiator, wherein the decomposition temperature of the first thermal initiator is 80-100°C; the decomposition temperature of the second thermal initiator is 100-130°C; and the decomposition temperature of the third thermal initiator is 140-160°C.

[0013] Optionally, the thermal initiator includes a first thermal initiator and a second thermal initiator, wherein the value of I ranges from 0.6 to 1.8; and the mass ratio of the first thermal initiator to the second thermal initiator is (1–2):(1–3). Alternatively, the thermal initiator may include the first thermal initiator and the third thermal initiator, wherein the value of I ranges from 0.7 to 2.0; and the mass ratio of the first thermal initiator to the third thermal initiator is (1–2):(1–4). Alternatively, the thermal initiator may include the second thermal initiator and the third thermal initiator, wherein the value of I ranges from 0.5 to 1.6; and the mass ratio of the second thermal initiator to the third thermal initiator is (1–3):(1–2). Alternatively, the thermal initiator may include the first thermal initiator, the second thermal initiator, and the third thermal initiator, wherein the value of I ranges from 0.8 to 2.0; and the mass ratio of the first thermal initiator, the second thermal initiator, and the third thermal initiator is (1–2):(1–3):(0.5–2).

[0014] Optionally, the first thermal initiator includes one or more of azobisisobutyronitrile and azobisisoheptanenitrile; And / or, the second thermal initiator includes one or more of dicumyl peroxide, tert-butyl peroxide (2-ethylhexanoate), and dimethyl azobisisobutyrate; And / or, the third thermal initiator includes one or more of di-tert-butyl peroxide or 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane and 1,3-bis(tert-butylperoxyisopropyl)benzene.

[0015] Optionally, the polymerization inhibitor includes one or more of p-methoxyphenol, tetramethylpiperidine oxide, p-benzoquinone, and 3,5-di-tert-butyl-4-hydroxytoluene.

[0016] Optionally, the electrolyte may also include lithium salt, non-aqueous organic solvent, and functional additives; with the total mass of the electrolyte as 100%, the lithium salt accounts for 8%–20% of the total mass of the electrolyte; the non-aqueous organic solvent accounts for 75%–90% of the total mass of the electrolyte; and the functional additives account for 0.5%–7% of the total mass of the electrolyte.

[0017] Another aspect of the present invention provides a battery comprising a positive electrode, a negative electrode, a separator, and the electrolyte described above.

[0018] The electrolyte provided by this invention, by precisely controlling the content and ratio (M / I) of polymerizable monomers (M%) and thermal initiators (I%) in the thermally triggered in-situ polymerization additive, can trigger the polymerization reaction only during abnormal temperature rise, remain stable at room temperature, and not affect the normal cycle performance of the battery; moreover, it rapidly forms a dense, continuous, and highly covert polymer separator film in the early stage of thermal runaway, effectively cutting off the exothermic chain reaction between the positive and negative electrodes; in addition, while ensuring high safety, it maintains good ionic conductivity and electrode / electrolyte interface stability of the electrolyte, avoiding rate performance degradation caused by excessive additives; at the same time, the additives can be directly dissolved in commercial carbonate electrolytes without changing the existing battery manufacturing process. Detailed Implementation

[0019] To make the technical problems solved, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.

[0020] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; the materials and reagents used are commercially available unless otherwise specified.

[0021] In one embodiment, the present invention provides an electrolyte comprising a thermally triggered in-situ polymerization additive, which includes a polymerizable monomer additive and a thermal initiator; taking the total mass of the electrolyte as 100%, the percentage content of the polymerizable monomer additive in the total mass of the electrolyte is M%, where M ranges from 0.4 to 5; the percentage content of the thermal initiator in the total mass of the electrolyte is 1%, where I ranges from 0.5 to 2; the values ​​of M and I satisfy the following conditions: Equation 1: 0.2≤M / I≤5.0.

[0022] Specifically, the value of M is any one point value or any two point values ​​from 0.4, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5.

[0023] When the value of M is in the range of 0.4-5, the polymerizable monomer additive can ensure the formation of a sufficiently thick and uniform polymer isolation layer in the early stage of thermal runaway. This layer can effectively block the contact between the electrode and the electrolyte without completely blocking the electrode pores, thus ensuring the ion transport channels. When the value of M is less than 0.4, the monomer concentration will be too low, making it impossible to form a continuous and dense polymer film, resulting in insufficient protection. When the value of M is greater than 5, the electrolyte viscosity will increase significantly, ion migration will be hindered, the battery rate performance will decrease, and excessive monomers may slowly self-polymerize at room temperature, affecting storage stability.

[0024] Specifically, the value of I is any one point value or any two point values ​​from 0.5, 0.8, 1.0, 1.2, 1.5, 1.8 or 2.0.

[0025] When the value of I is in the range of 0.5-2, active free radicals can be efficiently generated at the thermal trigger temperature to initiate a rapid and controllable polymerization reaction, achieving "on-demand film formation". When the value of I is less than 0.5, it will lead to insufficient initiation efficiency, slow or incomplete polymerization reaction, and difficulty in forming an effective isolation layer within the critical window of thermal runaway. When the value of I is greater than 2, it will lead to partial decomposition of the thermal initiator at room temperature, generating free radicals to initiate premature polymerization, reducing the long-term storage stability of the electrolyte, and may also lead to excessive polymer crosslinking and increased brittleness due to excessively high free radical concentration, affecting the flexibility and adhesion of the film.

[0026] Specifically, the M / I ratio is any one value or a range of any two values ​​from 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5.

[0027] When the M / I ratio is 0.2–5.0, a polymer barrier layer with moderate polymerization rate, uniform molecular weight distribution, dense film structure, and moderate elasticity can be achieved. This effectively blocks thermal runaway chain reactions without significantly sacrificing the electrochemical performance of the battery. When the M / I ratio is less than 0.2 (i.e., the initiator is relatively excessive), the free radical concentration will be too high, the polymerization reaction will be too violent, and low molecular weight, highly cross-linked or brittle polymers will be formed. The film will be prone to cracking, and residual free radicals may attack electrolyte components, exacerbating side reactions. When the M / I ratio is greater than 5.0 (i.e., the monomer is relatively excessive), the initiator is insufficient to fully activate all monomers, resulting in incomplete polymerization and the formation of a loose, porous or discontinuous polymer network. This cannot effectively isolate the exothermic reaction at the electrode / electrolyte interface, and the safety protection will fail.

[0028] This invention precisely controls the content and ratio (M / I) of polymerizable monomers (M%) and thermal initiators (I%) in the thermally triggered in-situ polymerization additive, enabling polymerization to occur only during abnormal temperature rises. It remains stable at room temperature and does not affect the normal cycle performance of the battery. Furthermore, it rapidly forms a dense, continuous, and highly covert polymer separator in the early stages of thermal runaway, effectively cutting off the exothermic chain reaction between the positive and negative electrodes. Additionally, while ensuring high safety, it maintains good ionic conductivity of the electrolyte and stability of the electrode / electrolyte interface, avoiding rate performance degradation due to excessive additives. Simultaneously, the additive can be directly dissolved in commercial carbonate electrolytes without altering existing battery manufacturing processes.

[0029] In one embodiment, the thermally triggered in-situ polymerization additive further includes a polymerization inhibitor, wherein the polymerization inhibitor accounts for R% of the total mass of the electrolyte, and the value of R ranges from 0.005 to 0.1; the M value, I value, and R value satisfy the following conditions: Equation 2: 10≤(M+I) / R≤500.

[0030] Specifically, the value of R is any one of the following: 0.005, 0.01, 0.02, 0.03, 0.05, 0.07, or 0.1, or a closed interval consisting of any two of these values.

[0031] When R is in the range of 0.005–0.1, it can effectively suppress the unexpected generation and chain growth of free radicals at room temperature or moderate temperature, significantly improve the chemical stability of the electrolyte during storage and battery cycling, and does not affect the initiation of high-temperature triggered polymerization reactions. When R is less than 0.005, it will lead to insufficient polymerization inhibition. The trace free radicals generated by the thermal initiator during long-term storage or high-temperature cycling may not be completely captured, causing premature polymerization of monomers, resulting in turbidity, increased viscosity, or even gelation of the electrolyte, affecting battery consistency and lifespan. When R is greater than 0.1, it will lead to excessive polymerization inhibitor. At the thermal runaway trigger temperature, the free radicals generated by the initiator need to consume a large amount of polymerization inhibitor before starting the polymerization reaction, significantly delaying the film formation time, and even failing to form an effective isolation layer due to the complete quenching of free radicals, thus losing the safety protection function.

[0032] Specifically, the ratio (M+I) / R is any one of the following values: 10, 20, 50, 100, 200, 300, 400, or 500, or a closed interval consisting of any two of these values.

[0033] When the (M+I) / R ratio is 10–500, under the premise of ensuring room temperature stability, the free radicals rapidly released by the thermal initiator at the thermal trigger temperature can quickly deplete the inhibitor and efficiently initiate monomer polymerization, achieving intelligent film-forming behavior of "delay controllable and rapid response". When the (M+I) / R ratio is less than 10, it indicates that the inhibitor is relatively excessive. Even at high temperatures, the free radicals are difficult to overcome the inhibitor's inhibitory effect, resulting in difficulty in initiating the polymerization reaction or an extremely low rate, making it impossible to form an effective protective film during the critical window of thermal runaway. When the (M+I) / R ratio is greater than 500, it indicates that the inhibitor content is too low, the system stability is insufficient, and unintended polymerization is likely to occur during battery manufacturing, storage, or high-temperature cycling, reducing the shelf life of the electrolyte and potentially forming uneven prepolymers on the electrode surface, interfering with SEI film formation and deteriorating electrochemical performance.

[0034] In a preferred embodiment, the value of M ranges from 1 to 4; the value of I ranges from 1 to 2; and the value of R ranges from 0.01 to 0.05. The values ​​of M, I, and R satisfy the following conditions: Equation 3: 0.5 ≤ M / I ≤ 2.0; Equation 4: 40≤(M+I) / R≤200.

[0035] When the M value and I value simultaneously satisfy Equation 3, it ensures that the ratio of monomer to initiator is well matched, which avoids violent burst polymerization and low molecular weight brittle film caused by excessive initiator, and also prevents incomplete polymerization or loose film caused by excess monomer, thereby forming an in-situ polymer isolation layer with high density, good adhesion and moderate flexibility. When the M, I, and R values ​​simultaneously satisfy Equation 4, the system exhibits excellent chemical inertness at room temperature (the polymerization inhibitor effectively suppresses free radical chain reactions). When the internal temperature of the battery rises to the thermal runaway threshold, the free radicals rapidly released by the thermal initiator can deplete the polymerization inhibitor in a short time, thereby efficiently initiating polymerization and ensuring that film formation is completed within the critical window of thermal runaway. Within this optimal parameter range, the electrolyte viscosity increase is small, the ionic conductivity retention rate is high, and the impact on the battery's room temperature / high temperature cycling, rate discharge, and storage performance is minimal. This achieves optimal synergy among polymerization reaction kinetics, film structure performance, and long-term electrolyte stability.

[0036] In one embodiment, the polymerizable monomer additive includes a C=C functional group and a functional side chain; the C=C functional group includes one or more of CH2=C(R)-COO-, CH2=CH-, CH2=CH-CH2-, or -C≡CH; the functional side chain includes -C n H 2n-1 (1≤n≤6), -O-, -F, -C n F 2n-1 (1≤n≤6), -OC n H 2n - (1≤n≤6), one or more of cyclic carbonates and -CN.

[0037] The C=C functional groups in the monomer (such as acrylate CH2=C(R)–COO-, vinyl CH2=CH–, etc.) can undergo electrochemically initiated polymerization on the positive electrode surface during the first charge of the battery, forming a cross-linked or linear polymer network. This polymer film is firmly anchored to the electrode surface, effectively inhibiting the continuous oxidative decomposition of the electrolyte, reducing gas generation and impedance growth. At the same time, since the polymerization reaction occurs at the electrode / electrolyte interface, the film thickness is controllable, dense and uniform, avoiding the problems of uneven or excessively thick films formed by traditional additives.

[0038] -C n H 2n-1 (1≤n≤6) provides hydrophobicity and flexibility, enhances the mechanical stretchability of the membrane, and alleviates volumetric stress during charging and discharging; -F, -C n F 2n-1 (1≤n≤6) Significantly enhances the membrane's antioxidant capacity and reduces interfacial side reactions; at the same time, it enhances thermal stability and hydrophobicity, and inhibits HF corrosion; -O- or -OC nH 2n - (1≤n≤6) Introducing lithophilic sites to promote Li + Desolvation and cross-interface transport reduce interfacial impedance; some structures can chelate metal ions and inhibit the dissolution of transition metals. Cyclic carbonate groups (such as ethylene carbonate derivatives) participate in the formation of SEI / CEI rich in inorganic-organic composite components such as Li2CO3 and ROCO2Li, thereby improving ionic conductivity and electronic insulation. -CN (cyano) exhibits a strong electron-withdrawing effect, lowering the LUMO energy level and preferentially reducing the film formation; it can also react with Li + Coordination, improving Li + Number of migrations.

[0039] The polymerizable monomer additive of the present invention integrates polymerizable double bonds and multifunctional side chains into a single monomer molecule, realizing a "one agent, multiple effects" interface regulation strategy. It can construct a mechanically / chemically stable polymer backbone through in-situ polymerization, and precisely regulate interface ion transport, antioxidant properties and metal passivation capabilities through side chain chemistry. It is particularly suitable for the interface stabilization requirements of high energy density lithium-ion batteries.

[0040] In one embodiment, the polymerizable monomer additive includes one or more of trifluoroethyl methacrylate (TFEMA), 1,3-dioxolane-2-one vinyl ether, allyl glycidyl ether, perfluorohexyl ethyl acrylate (HFPA), and 2-vinyl-1,3-dioxolane.

[0041] By using trifluoroethyl methacrylate (TFEMA) and perfluorohexyl ethyl acrylate (HFPA), a composite CEI membrane with both high ionic conductivity and strong antioxidant capacity can be constructed; by using allyl glycidyl ether, epoxy / ether functional groups can be introduced to enhance interfacial adhesion and Li + Transport kinetics; perfluorohexyl ethyl acrylate and 2-vinyl-1,3-dioxolane are selected; multi-monomer copolymerization achieves a gradient interface layer with tunable structure and complementary functions; avoids the defects of high brittleness or high impedance of single-component films.

[0042] In one embodiment, the thermal initiator includes at least two of a first thermal initiator, a second thermal initiator, and a third thermal initiator, wherein the decomposition temperature of the first thermal initiator is 80-100°C; the decomposition temperature of the second thermal initiator is 100-130°C; and the decomposition temperature of the third thermal initiator is 140-160°C.

[0043] This scheme utilizes the synergistic effect of three thermal initiators with different decomposition temperatures to enable polymerizable monomers to initiate free radical polymerization on demand and in an orderly manner within their respective temperature ranges: the low-temperature initiator decomposes first at 80–100℃, generating free radicals, triggering initial monomer polymerization, forming an initial barrier layer, and inhibiting the spread of early side reactions; the medium-temperature initiator releases a large number of free radicals at 100–130℃, driving the main polymerization reaction, rapidly generating a dense polymer network, effectively sealing electrode pores and passivating active surfaces; the high-temperature initiator above 140℃ serves as a "last line of defense." This ensures that polymerization and sealing can be completed even under extreme temperature rises, preventing a full-scale outbreak of thermal runaway chain reactions. By introducing a combination of thermal initiators containing at least two different decomposition temperature levels (i.e., first thermal initiator: 80–100℃; second thermal initiator: 100–130℃; third thermal initiator: 140–160℃) into the electrolyte or electrode coating, this embodiment constructs a multi-level response, gradient-triggered in-situ polymerization thermal protection mechanism, which significantly improves the active safety performance of lithium-ion batteries in the early stages of abnormal temperature rise or thermal runaway.

[0044] In one embodiment, the thermal initiator includes a first thermal initiator and a second thermal initiator, where the value of I ranges from 0.6 to 1.8; and the mass ratio of the first thermal initiator to the second thermal initiator is (1–2):(1–3).

[0045] Specifically, the mass ratio of the first thermal initiator and the second thermal initiator is any one of 1:1, 1:2, 1:3, 2:1 or 2:3 or a range of any two ratios; in a preferred embodiment, the mass ratio of the first thermal initiator and the second thermal initiator is 1:(1-2).

[0046] When the mass ratio of the first thermal initiator to the second thermal initiator is (1–2):(1–3), the system has good initiation efficiency and reaction stability, can achieve uniform crosslinking, control the exothermic rate, and effectively improve the mechanical properties and thermal stability of the final product; however, if the mass ratio is less than 1:3 (i.e., the second thermal initiator is excessive), the initiation rate will be too slow, the reaction will be incomplete, and even local uncured areas will appear, thereby reducing the overall performance of the material; if the mass ratio is greater than 2:1 (i.e., the first thermal initiator is excessive), it may cause violent exothermic reactions, local overheating, or an increase in side reactions, resulting in material embrittlement, darkening of color, or decreased storage stability.

[0047] In addition, when the mass ratio is within the above preferred range (1–2): (1–3), but parameter I is less than 0.6, the system activity is insufficient and it is difficult to fully start the polymerization reaction at the set temperature; while when I is greater than 1.8, the reaction may run out of control due to the excessive total amount of initiator and the gel time may be too short, which is not conducive to process operation and product consistency control.

[0048] In one embodiment, the thermal initiator includes a first thermal initiator and a third thermal initiator, and the value of I ranges from 0.7 to 2.0; the mass ratio of the first thermal initiator to the third thermal initiator is (1–2):(1–4). Specifically, the mass ratio of the first thermal initiator to the third thermal initiator is any one of 1:1, 1:2, 1:3, 1:4, 2:1 or 2:3 or a range of any two ratios; in a preferred embodiment, the mass ratio of the first thermal initiator to the third thermal initiator is (1–2):(2–3).

[0049] When the mass ratio of the first thermal initiator to the third thermal initiator is within the range of (1–2):(1–4), the system can achieve a synergistic initiation effect: on the one hand, it takes into account both the low-temperature initial activity and the high-temperature continuous decomposition ability, and on the other hand, it effectively controls the exothermic peak shape and gel time, thereby obtaining a product with uniform curing, low internal stress and excellent mechanical properties; however, if the mass ratio is less than 1:4 (i.e. the third thermal initiator is significantly excessive), it will lead to insufficient initial initiation activity, excessively long reaction induction period, and even difficulty in complete cross-linking at conventional curing temperatures, resulting in sticky material surface or substandard physical properties; if the mass ratio is greater than 2:1 (i.e. the first thermal initiator is excessive), it may cause violent exothermic reaction due to excessively rapid decomposition at low temperature, leading to local coking, bubble generation or decreased storage stability, which is not conducive to process control and product consistency.

[0050] Furthermore, even if the mass ratio of the first thermal initiator to the third thermal initiator is within the preferred range of (1–2): (1–4), if parameter I is less than 0.7, the overall amount of initiator is too low, and the system is difficult to complete sufficient polymerization within the set process window, resulting in insufficient conversion rate; while when I is greater than 2.0, the total amount of initiator is too high, which may not only cause the reaction rate to run away from control and shorten the service life, but may also affect the long-term thermal stability and electrical properties of the material due to the increase of residual small molecule by-products.

[0051] In one embodiment, the thermal initiator includes a second thermal initiator and a third thermal initiator, and the value of I ranges from 0.5 to 1.6; the mass ratio of the second thermal initiator to the third thermal initiator is (1–3):(1–2). Specifically, the mass ratio of the second thermal initiator to the third thermal initiator is any one of 1:1, 1:2, 2:1, 3:1 or 3:2 or any two of these ratios; in a preferred embodiment, the mass ratio of the second thermal initiator to the third thermal initiator is (2-3):(1-2).

[0052] When the mass ratio of the second thermal initiator to the third thermal initiator is (1–3):(1–2), the two complement each other well in terms of decomposition temperature and free radical release rate: the second thermal initiator provides stable initiation ability in the mid-temperature stage, while the third thermal initiator provides continuous energy at higher temperatures, thereby achieving wide-temperature-range, gradient curing, effectively inhibiting explosive polymerization, reducing internal stress, and improving the crosslinking density and heat distortion temperature of the final material; if the mass ratio is less than 1:2 (i.e., the third thermal initiator is relatively excessive), it will lead to insufficient low-temperature initiation activity, delayed reaction initiation, and incomplete curing, especially under medium and low temperature process conditions, which may easily lead to poor surface drying or low mechanical strength; if the mass ratio is greater than 3:1 (i.e., the second thermal initiator is significantly excessive), it may cause violent exothermic reaction due to excessively high free radical concentration in the mid-temperature stage, resulting in local overheating, microcrack generation, or decreased storage stability, which is not conducive to the quality control of thick products or continuous production.

[0053] Furthermore, even if the mass ratio of the second thermal initiator to the third thermal initiator is within the preferred range of (1–3): (1–2), if parameter I is less than 0.5, the overall amount of initiator is insufficient, making it difficult to drive full polymerization, resulting in low conversion rate, increased residual monomers, and affecting the chemical resistance and long-term performance of the material. When I is greater than 1.6, the total amount of initiator is too high, which not only shortens the pot life, but may also cause yellowing, embrittlement, or deterioration of electrical insulation properties of the material due to aggravated side reactions or accumulation of small molecule decomposition products.

[0054] In one embodiment, the thermal initiator includes a first thermal initiator, a second thermal initiator and a third thermal initiator, and the value of I ranges from 0.8 to 2.0; the mass ratio of the first thermal initiator, the second thermal initiator and the third thermal initiator is (1–2):(1–3):(0.5–2).

[0055] Specifically, the mass ratio of the first thermal initiator, the second thermal initiator, and the third thermal initiator is any one of the following ratios or a range of any two ratios: 1:1:0.5, 1:1:1, 1:1:2, 1:2:0.5, 1:2:1, 1:2:2, 1:3:0.5, 1:3:1, 1:3:2, 2:1:0.5, 2:1:1, 2:1:2, 2:2:0.5, 2:2:1, 2:2:2, 2:3:0.5, 2:3:1, or 2:3:2; in a preferred embodiment, the mass ratio of the first thermal initiator, the second thermal initiator, and the third thermal initiator is (1–2):(2–3):(1–2).

[0056] When the mass ratio of the first, second, and third thermal initiators is (1–2):(1–3):(0.5–2), the three initiators exhibit a gradient synergistic effect in terms of decomposition temperature, free radical release rate, and reactivity: the first thermal initiator provides low-temperature initial activity, ensuring timely reaction initiation; the second thermal initiator maintains stable initiation during the mid-temperature stage, ensuring smooth progress of the main crosslinking process; and the third thermal initiator continuously provides energy in the high-temperature later stage, promoting deep curing and network improvement. This enables wide-temperature-range, staged, and controllable exothermic curing. The behavior significantly improves the crosslinking uniformity, mechanical strength, thermal stability and process adaptability of the material; when the mass ratio is less than 1:3:2, the low-temperature initiation ability of the system is insufficient, the induction period is prolonged, and poor surface drying, incomplete curing or increased internal residual monomers are likely to occur, especially in low-temperature or rapid curing processes; when the mass ratio is greater than 2:1:0.5, the initial free radical concentration is too high, which causes violent exothermic or even explosive polymerization, resulting in local coking, bubbles, microcracks or decreased storage stability. At the same time, the insufficient initiation ability in the later stage affects the final conversion rate and heat resistance.

[0057] Furthermore, even if the mass ratio of the three components is within the above-mentioned preferred range (1–2):(1–3):(0.5–2), if parameter I is less than 0.8, the total amount of initiator is too low, making it difficult to drive sufficient polymerization, resulting in excessively long gelation time and insufficient crosslinking density, which in turn affects the mechanical properties, solvent resistance, and long-term reliability of the material. When I is greater than 2.0, the total amount of initiator is too high, which not only significantly shortens the pot life, but may also cause problems such as yellowing, embrittlement, decreased electrical properties, or excessive odor / volatile matter due to aggravated side reactions and accumulation of small molecule decomposition products.

[0058] In one embodiment, the first thermal initiator includes one or more of azobisisobutyronitrile (AIBN) and azobisisoheptanenitrile (ABVN); And / or, the second thermal initiator includes one or more of benzoyl peroxide (BPO), dicumyl peroxide (DCP), tert-butyl peroxide (2-ethylhexanoate) (TBPEH), and dimethyl azobisisobutyrate (AIBME); And / or, the third thermal initiator includes one or more of di-tert-butyl peroxide (DTBP) or 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane (TMCH) and 1,3-bis(tert-butylperoxyisopropyl)benzene (BIPB).

[0059] This invention constructs a multi-level thermal safety protection system with temperature gradient response, controllable free radical release, and precise polymerization triggering by precisely selecting a specific combination of thermal initiators with a clear decomposition temperature window—including at least two of the following: a first thermal initiator (azobisisobutyronitrile AIBN, azobisisoheptanenitrile ABVN), a second thermal initiator (dicumyl peroxide DCP, tert-butyl peroxide TBPO, dimethyl azobisisobutyrate MAIB), and a third thermal initiator (di-tert-butyl peroxide DTBP, 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane TMCH, 1,3-bis(tert-butylperoxyisopropyl)phenyl BIPB).

[0060] The first thermal initiator is activated at the initial stage of SEI film collapse and local micro-short circuit heat generation, triggering monomer oligomerization or nucleation to form a preliminary passivation layer and suppressing the chain reaction amplification. The second thermal initiator corresponds to the window of intense exothermic reaction between the negative electrode and the electrolyte, releasing a large number of free radicals, driving the rapid cross-linking of polymerizable monomers to generate a dense polymer network, effectively sealing electrode pores and isolating the active interface. The third thermal initiator can still decompose stably under extreme conditions such as membrane shrinkage and oxygen release from the positive electrode, serving as the "ultimate insurance" to ensure that even if the first two levels of protection fail, the final polymerization and sealing can still be completed, delaying the thermal runaway. The use of the above initiators significantly improves the thermal safety performance of the battery and delays or even blocks the thermal runaway process.

[0061] The initiator of this invention is extremely stable at room temperature (≤60℃) and under normal storage / cycling conditions, does not self-decompose, and does not negatively affect battery first-efficiency, cycle life, impedance, or gas generation; free radical polymerization is only initiated sequentially when the temperature abnormally rises to a preset threshold, achieving a completely passive, intelligent thermal response without external signals; compared with adding flame-retardant solvents or inorganic fillers, this strategy does not sacrifice electrolyte ionic conductivity or wettability, and solves the inherent contradiction of traditional safety additives "trading performance for safety".

[0062] In one embodiment, the polymerization inhibitor includes one or more of p-methoxyphenol (MEHQ), tetramethylpiperidine oxide, p-benzoquinone, and 3,5-di-tert-butyl-4-hydroxytoluene.

[0063] By introducing phenolic or nitroxide radical inhibitors with free radical scavenging capabilities, dual regulation of the thermoresponsive polymerization system was successfully achieved: at room temperature, it acts as a "stabilizer" to remove stray free radicals and ensure the long-term storage stability and electrochemical compatibility of the electrolyte; at high temperature, it acts as a "depletable insurance" to automatically release the inhibition and release the polymerization protection function when the thermal runaway warning temperature is "flooded" by the free radical flood.

[0064] In one embodiment, the electrolyte also includes lithium salt, non-aqueous organic solvent, and functional additives; with the total mass of the electrolyte as 100%, the lithium salt accounts for 8%–20% of the total mass of the electrolyte; the non-aqueous organic solvent accounts for 75%–90% of the total mass of the electrolyte; and the functional additives account for 0.5%–7% of the total mass of the electrolyte.

[0065] Specifically, the lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium difluorophosphate, lithium bis(oxalate)borate, lithium difluorooxalateborate, lithium tetrafluoroborate, and lithium difluorodi(oxalate)borate; the percentage of lithium salt in the total mass of the electrolyte is any one value or a range of any two values ​​from 8%, 10%, 12.5%, 15%, 17.5%, or 20%; in a preferred embodiment, the percentage of lithium salt in the total mass of the electrolyte is 10%–15%; when the lithium salt percentage is within this range, high ionic conductivity, good low-temperature performance, and passivation capability of aluminum current collectors can be balanced, while avoiding a sharp increase in viscosity or cost due to excessively high concentration.

[0066] Specifically, the non-aqueous organic solvent includes one or more of ethylene carbonate, diethyl carbonate, methyl ethyl carbonate, dimethyl carbonate, and fluoroethylene carbonate; the percentage of the non-aqueous organic solvent in the total mass of the electrolyte is any one or a range of any two values ​​from 75%, 77.5%, 80%, 82.5%, 85%, 87.5%, or 90%; in a preferred embodiment, the percentage of the non-aqueous organic solvent in the total mass of the electrolyte is 80%–87.5%. When the proportion of the non-aqueous organic solvent is within this range, it ensures that the electrolyte has excellent wettability, low viscosity, and a wide electrochemical window, which is beneficial for efficient lithium-ion migration and sufficient wetting of the electrodes / separator.

[0067] Specifically, the functional additives include one or more of film-forming additives and HF scavengers; the film-forming additives include one or more of fluoroethylene carbonate (FEC), vinylene carbonate (VC), and ethylene sulfate (DTD), which are used to preferentially reduce / oxidize and form a stable SEI / CEI film on the surface of the negative or positive electrode. The HF scavenger includes one or more of tris(trimethylsilyl)phosphate (TMSPa), tris(trimethylsilyl)phosphite (TMSPi), and alkaline ionic liquids, used to remove HF generated by the hydrolysis of LiPF6 from the electrolyte; the functional additive accounts for a percentage of 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, or 7% of the total electrolyte mass, or a range of any two of these percentages; in a preferred embodiment, the functional additive accounts for 1%–5% of the total electrolyte mass; when the percentage of functional additive is within this range, it can trigger effective polymerization protection under thermal anomalies and maintain interfacial stability at room temperature, while avoiding excessive addition that could lead to a decrease in ionic conductivity or an increase in side reactions.

[0068] In one embodiment, another aspect of the present invention provides a battery comprising a positive electrode, a negative electrode, a separator, and the electrolyte described above.

[0069] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector, the positive active material layer including a positive active material, a positive conductive agent and a positive binder; In some embodiments, the positive electrode active material includes at least one of lithium nickel cobalt manganese oxide (NCM, such as NCM111, NCM523, NCM622, NCM811), lithium nickel cobalt aluminum oxide (NCA), lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, and lithium-rich manganese-based materials.

[0070] In some embodiments, the positive electrode conductive agent includes at least one of carbon materials such as natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene.

[0071] In some embodiments, the positive electrode binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose.

[0072] In some embodiments, the type of positive electrode current collector is not particularly limited, and it can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metallic materials such as lanthanum, stainless steel, lanthanum plating, titanium, and tantalum, as well as carbon materials such as carbon cloth and carbon paper. In one embodiment, the positive electrode current collector is a metallic material.

[0073] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector; the negative electrode active material layer includes a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder.

[0074] In some embodiments, the negative electrode active material includes one or more of graphite, silicon-carbon composite materials, or lithium metal materials; the negative electrode active material is preferably designed in conjunction with the positive electrode and functionalized electrolyte to maximize the overall performance of the battery.

[0075] In some embodiments, the negative electrode conductive agent includes at least one of carbon materials such as natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene.

[0076] In some embodiments, the negative electrode binder includes at least one of styrene-butadiene latex and CMC.

[0077] In some embodiments, there are no particular limitations on the negative electrode current collector, as long as it can achieve the purpose of this application. For example, it can be at least one of copper foil, copper alloy foil, lanthanum foil, stainless steel foil, titanium foil, foamed lanthanum, foamed copper, or composite current collector; in some preferred embodiments, the negative electrode current collector includes copper foil.

[0078] In some embodiments, the diaphragm is a porous polymer film selected from polyethylene (PE), polypropylene (PP) single-layer film, or PE / PP / PE three-layer composite film. Preferably, the diaphragm surface may be coated with a ceramic or polymer coating to improve thermal stability and electrolyte wettability.

[0079] The above-mentioned negative electrode, positive electrode and separator are assembled into a cell by stacking or winding in a "positive-separator-negative" manner, electrolyte is injected, and after formation, aging and capacity testing, it is packaged in an aluminum-plastic film soft pack, steel shell or aluminum shell to obtain a lithium-ion battery.

[0080] The battery of the present invention can be used in consumer electronics (such as smartphones and laptops), electric vehicles (such as electric vehicles and electric bicycles), and energy storage systems (such as grid energy storage and home energy storage).

[0081] The beneficial effects of the present invention will be further illustrated below with reference to the embodiments.

[0082] To make the inventive objectives, technical solutions, and beneficial effects of this invention clearer, the invention is further described in detail below with reference to embodiments. However, it should be understood that the embodiments of this invention are merely for illustrative purposes and not for limiting the invention, and the embodiments are not limited to those given in the specification. Materials not specified in the embodiments were prepared under conventional conditions or according to the conditions recommended by the material supplier.

[0083] Furthermore, it should be understood that the one or more method steps mentioned in this invention do not preclude the existence of other method steps before or after the combination steps, or the insertion of other method steps between these explicitly mentioned steps, unless otherwise stated. It should also be understood that the combination connection relationship between one or more devices / apparatus mentioned in this invention does not preclude the existence of other devices / apparatus before or after the combination of devices / apparatus, or the insertion of other devices / apparatus between these explicitly mentioned devices / apparatus, unless otherwise stated. Moreover, unless otherwise stated, the numbering of each method step is merely a convenient tool for identifying each method step, and not for limiting the order of the method steps or limiting the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the invention.

[0084] In the following embodiments, the reagents, materials and instruments used, unless otherwise specified, are commercially available or can be obtained through synthesis methods known in the art.

[0085] Table 1. Design of parameters for thermally triggered in-situ polymerization additives in the electrolytes of Examples 1-49 and Comparative Examples 1-8; Continued from Table 1 Continued from Table 1 Example 1 This embodiment illustrates the electrolyte and battery disclosed in this invention; it includes the following operational steps: Preparation of electrolyte Ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate were mixed in a volume ratio of 3:5:2 as the base organic solvent. Lithium hexafluorophosphate was added to prepare a 1.2 mol / L solution. Subsequently, 2% (w / w) of vinylene carbonate was added as a conventional film-forming additive.

[0086] Finally, the multi-stage thermally responsive additive system of the present invention is added, with the specific types and mass percentages as follows: Polymerizable monomer additive: Trifluoroethyl methacrylate (TFEMA), added at a rate of 3.0%.

[0087] Thermal initiation additives: dicumyl peroxide (DCP), 0.6%; di-tert-butyl peroxide (DTBP), 0.4%.

[0088] Polymerization inhibitor: p-methoxyphenol (MEHQ), added at a rate of 0.05%.

[0089] All components were stirred at room temperature until completely dissolved and homogeneous to obtain the safe electrolyte of the present invention. Calculations show that M / I (total mass ratio of monomer to initiator) is 3 and (M+I) / R (mass ratio of polymerization system to inhibitor) is 80, both of which are within the preferred range.

[0090] Preparation of positive electrode sheet The positive electrode active material NCM811, conductive agent acetylene black, and binder polyvinylidene fluoride were mixed at a mass ratio of 96:2:2. An appropriate amount of N-methyl-2-pyrrolidone solvent was added, and the mixture was stirred evenly in a vacuum mixer to obtain a positive electrode slurry with a solid content of approximately 70%. The slurry was evenly coated on both sides of an aluminum foil current collector, dried in an oven, rolled, and cut to obtain the positive electrode sheet.

[0091] Preparation of negative electrode sheet Artificial graphite (negative electrode active material), acetylene black (conductive agent), sodium carboxymethyl cellulose (thickener), and styrene-butadiene rubber (binder) were mixed in a mass ratio of 96:1:1.5:1.5. Deionized water solvent was added, and the mixture was stirred evenly in a vacuum mixer to obtain a negative electrode slurry. The slurry was evenly coated on both sides of a copper foil current collector, dried in an oven, rolled, and cut to obtain the negative electrode sheet.

[0092] Preparation of diaphragm PE porous polymer film is used as the membrane substrate; Battery manufacturing: The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. The cells are then wound to form bare cells, which are then placed in an aluminum-plastic film shell and vacuum-baked at 85°C for 24 hours. The electrolyte is then injected, and the cells undergo standard processes such as vacuum sealing, settling, formation, aging, and capacity testing to produce soft-pack lithium-ion batteries.

[0093] Example 2-49 Examples 2-49 illustrate the electrolyte and battery disclosed in this invention, including most of the operating steps in Example 1, with the following differences: The parameters of the thermally triggered in-situ polymerization additive in the electrolyte, as shown in Table 1, were used.

[0094] Comparative Examples 1-8 Comparative Examples 1-8 are used to illustrate the electrolyte and battery disclosed in this invention, including most of the operating steps in Example 1, the difference being: The parameters of the thermally triggered in-situ polymerization additive in the electrolyte, as shown in Table 1, were used.

[0095] Performance testing The following performance tests were performed on the batteries prepared in Examples 1-49 and Comparative Examples 1-8: The lithium-ion batteries prepared in the above embodiments and comparative examples were tested as follows: 0℃ Cyclic Performance Test The lithium-ion batteries prepared in the above embodiments and comparative examples were cycle-tested at 0°C according to a charge-discharge regime of 1C constant current and constant voltage charging to 4.52V (cutoff current 0.05C) and 1C constant current discharging to 3.0V. The discharge capacity of the first week was recorded as Y1, and the discharge capacity of the Nth week was recorded as Y2; the capacity retention rate of the Nth week was calculated as Y2 / Y1. The cycle number when the capacity retention rate first dropped to 80% was recorded as N@0°C.

[0096] 25℃ Cyclic Performance Test The lithium-ion batteries prepared in the above embodiments and comparative examples were cycle-tested at 25°C according to a charge-discharge regime of 1C constant current and constant voltage charging to 4.52V (cutoff current 0.05C) and 1C constant current discharging to 3.0V. The discharge capacity of the first week was recorded as C1, and the discharge capacity of the Nth week was recorded as C2; the capacity retention rate of the Nth week was calculated as C2 / C1. The cycle number when the capacity retention rate first dropped to 80% was recorded as N@25°C.

[0097] Thermal shock performance test The lithium-ion batteries were charged to 4.52V (cutoff current 0.05C) at a constant temperature of 25±2℃. Then, the fully charged batteries were placed in a thermal shock test chamber and heated from room temperature to 135±2℃ at a heating rate of 5℃ / min, and held at this temperature for 1 hour. The center temperature of the batteries was recorded throughout the heating and holding process. Five batteries were tested in each group.

[0098] The test results are shown in Table 2.

[0099] Table 2 Battery Electrochemical Performance Continued from Table 2 Comparing Examples 1-5 and Comparative Examples 1-2, it can be seen that when the value of M is in the range of 0.4-5, after 280-340 cycles at 0°C and 720-830 cycles at 25°C, the polymerizable monomer additive does not completely block the electrode pores, ensuring the ion transport channels. The battery exhibits a long cycle life at both 0°C and 25°C, and passes all thermal shocks at 135°C with a core temperature of 148-162°C. This indicates that the polymerizable monomer additive can ensure the formation of a sufficiently thick and uniform polymer isolation layer in the early stages of thermal runaway, improving... Battery safety and electrochemical performance: When the value of M is less than 0.4, the cycle life is significantly reduced after 180 cycles at 0℃ and 520 cycles at 25℃. During thermal shock, both batteries caught fire with a center temperature of 185℃, indicating that the monomer concentration is too low and cannot form a continuous and dense polymer film, resulting in insufficient protection. When the value of M is greater than 5, the cycle life is reduced to only 220 cycles at 0℃ and 580 cycles at 25℃. During thermal shock, one battery caught fire, and the overall performance deteriorated significantly.

[0100] Comparing Example 1 and Comparative Example 7, it can be seen that when the electrolyte contains polymerizable monomer additives, the battery can cycle for 335 cycles at 0°C and 825 cycles at 25°C. The monomers can form an effective polymerizable protective layer under thermal triggering, ensuring ion conduction and interface stability. The battery has excellent cycle life at 0°C and 25°C, passes all 135°C thermal shocks, and has a center temperature of 148°C, demonstrating excellent safety and electrochemical performance. When the electrolyte does not contain polymerizable monomer additives, the battery can cycle for 210 cycles at 0°C and 570 cycles at 25°C, resulting in a significant decrease in cycle life. During thermal shock, four batteries catch fire, and the center temperature rises to 190°C. Due to the lack of a polymerizable protective layer, thermal safety is completely compromised.

[0101] Comparing Example 1 and Comparative Example 6, it can be seen that when the electrolyte contains polymerizable monomer additives, thermal initiators, and polymerization inhibitors simultaneously, the electrolyte achieves 335 cycles at 0°C and 825 cycles at 25°C. The three work synergistically to achieve controlled in-situ polymerization, resulting in a stable interface and sufficient thermal protection. All samples passed the 135°C thermal shock test, with a core temperature of 148°C, demonstrating excellent balance between electrochemical and safety performance. However, when the electrolyte does not contain polymerizable monomer additives, thermal initiators, and polymerization inhibitors, the electrolyte achieves 200 cycles at 0°C and 550 cycles at 25°C, resulting in a significantly reduced cycle life. All samples ignited during the thermal shock test, with temperatures exceeding 500°C, and the electrolyte offered no thermal protection.

[0102] Comparing Examples 1, 6-8, and Comparative Example 3, it can be seen that when the mass ratio of the second thermal initiator to the third thermal initiator is within the preferred range of (1–3): (1–2), and the value of I is in the range of 0.5–1.6, the initiation efficiency is moderate, the polymerization rate is controllable, the electrode interface is not damaged, the cycle life is excellent, all thermal shocks at 135°C are passed, the center temperature is 148–158°C, and the electrochemical and safety performance is balanced and excellent. When the value of I is less than 0.5, the initiation is insufficient, the polymerization is incomplete, three electrodes ignite during thermal shock, the center temperature is 180°C, and the protection fails. When the value of I is greater than 1.6, the initiation is excessive, leading to an increase in side reactions, a decrease in cycle life, and a decline in thermal safety performance, after 275 cycles at 0°C and 710 cycles at 25°C.

[0103] Comparing Examples 1 and 10-13, it can be seen that when the mass ratio of the second thermal initiator to the third thermal initiator is (1–3):(1–2), the initiation synergy is optimal after 330-335 cycles at 0°C and 818-825 cycles at 25°C, resulting in more uniform polymerization, optimal battery cycle and thermal safety performance, and a thermal shock center temperature of 148-151°C at 135°C. If the mass ratio of the second thermal initiator to the third thermal initiator is less than 1:2, the initiation matching degree decreases after 328 cycles at 0°C and 815 cycles at 25°C, and the cycle life is slightly reduced. If the mass ratio of the second thermal initiator to the third thermal initiator is greater than 3:1, the initiation system becomes unbalanced after 315 cycles at 0°C and 790 cycles at 25°C, and both cycle life and thermal safety decline.

[0104] Comparative examples 14-18 show that when the mass ratio of the first thermal initiator to the second thermal initiator is (1–2):(1–3), and the value of I is in the range of 0.6–1.8, the initiation system is stable and controllable after 300–338 cycles at 0℃ and 770–828 cycles at 25℃, the polymerization is mild and does not damage the interface, the cycle life is excellent, and all thermal shocks at 135℃ are passed. When the value of I is less than 0.6, the initiation is insufficient after 285 cycles at 0℃ and 735 cycles at 25℃, the polymerization is incomplete, and the cycle and thermal safety performance decreases. When the value of I is greater than 1.8, the initiation is excessive after 315 cycles at 0℃ and 792 cycles at 25℃, resulting in interface deterioration, reduced cycle life, and increased thermal shock temperature.

[0105] Comparing Examples 14 and 19-22, it can be seen that when the mass ratio of the first thermal initiator to the second thermal initiator is (1–2):(1–3), the initiation matching is optimal after 333-338 cycles at 0°C and 822-828 cycles at 25°C, resulting in the best polymerization protection effect and a lower thermal shock center temperature. When the mass ratio of the first thermal initiator to the second thermal initiator is less than 1:3, the initiation efficiency decreases after 322 cycles at 0°C and 802 cycles at 25°C, the cycle life is slightly reduced, and the thermal shock temperature increases. When the mass ratio of the first thermal initiator to the second thermal initiator is greater than 2:1, the initiation ratio becomes unbalanced after 330 cycles at 0°C and 818 cycles at 25°C, the cycle decay accelerates, and the safety performance deteriorates.

[0106] Comparing Examples 23-26 and Comparative Example 4, it can be seen that when the mass ratio of the first thermal initiator to the third thermal initiator is within the preferred range of (1–2):(1–4), and the value of I is in the range of 0.7–2, the initiation rhythm is matched after 305-328 cycles at 0℃ and 775-815 cycles at 25℃, the polymerization is uniform and controllable, the cycle life is excellent, and all cycles pass the 135℃ thermal shock. When the value of I is less than 0.7, the initiation is insufficient after 280 cycles at 0℃ and 725 cycles at 25℃, the polymer layer is not dense, and the cycle and safety performance decreases. When the value of I is greater than 2.0, the initiation is violent after 150 cycles at 0℃ and 450 cycles at 25℃, resulting in interface damage. Four of them catch fire during the thermal shock, with a center temperature of 186℃, and safety fails.

[0107] Comparing Examples 24 and 27-30, it can be seen that when the mass ratio of the first thermal initiator to the third thermal initiator is in the range of (1–2):(1–4), the initiation synergy is stable after 322-328 cycles at 0°C and 805-815 cycles at 25°C, the polymer layer is continuous and dense, and the battery cycle and thermal safety performance are excellent. If the mass ratio of the first thermal initiator to the third thermal initiator is less than 1:4, the initiation efficiency decreases after 318 cycles at 0°C and 798 cycles at 25°C, the cycle life decreases slightly, and the thermal shock temperature increases. If the mass ratio of the first thermal initiator to the third thermal initiator is greater than 2:1, the initiation ratio is unbalanced after 320 cycles at 0°C and 800 cycles at 25°C, and the overall performance declines.

[0108] Comparing Examples 31-34 and Comparative Example 5, it can be seen that when the mass ratio of the first thermal initiator, the second thermal initiator, and the third thermal initiator is (1–2):(1–3):(0.5–2), and the value of I is in the range of 0.8–2, the three-stage initiation matching is optimal after 308-330 cycles at 0℃ and 778-820 cycles at 25℃, resulting in mild and controllable polymerization, high cycle life, and passing all 135℃ thermal shocks. If the value of I is less than 0.8, the initiation is insufficient after 272 cycles at 0℃ and 705 cycles at 25℃, resulting in weak protection and decreased cycle and safety performance. When the value of I is greater than 2.0, the initiation is severely damaged after 140 cycles at 0℃ and 420 cycles at 25℃, and all thermal shocks cause fires, with temperatures exceeding 500℃, resulting in complete loss of control.

[0109] Comparative examples 34-39 show that when the mass ratio of the first thermal initiator, the second thermal initiator, and the third thermal initiator is (1–2):(1–3):(0.5–2), the initiation system is most stable after 322-330 cycles at 0°C and 808-820 cycles at 25°C, resulting in a uniform and dense polymer layer and optimal cycling and thermal safety. When the mass ratio of the first thermal initiator, the second thermal initiator, and the third thermal initiator is less than 1:3:2, the initiation synergy decreases after 320-322 cycles at 0°C and 805-808 cycles at 25°C, the cycle life decreases slightly, and the thermal shock temperature increases. When the mass ratio of the first thermal initiator, the second thermal initiator, and the third thermal initiator is greater than 2:1:0.5, the initiation ratio becomes unbalanced after 318 cycles at 0°C and 802 cycles at 25°C, the cycle decay accelerates, and the safety performance deteriorates.

[0110] Comparing Examples 1, 20, and 47-49, it can be seen that when the thermal initiator includes at least two of the first, second, and third thermal initiators, the cycle time is 335-336 cycles at 0°C and 825-826 cycles at 25°C. The multiple initiators synergistically broaden the response temperature range, resulting in more complete and uniform polymerization, longer cycles, and lower thermal shock center temperature. When the thermal initiator includes only one type, the cycle time is 290-305 cycles at 0°C and 745-765 cycles at 25°C. The initiation is singular and the response is narrow, resulting in insufficient polymerization, decreased cycle time, increased thermal shock temperature, and weakened safety performance.

[0111] Comparing Example 1 and Comparative Example 8, it can be seen that when a thermal initiator is present in the electrolyte, cycling at 0°C for 335 cycles and at 25°C for 825 cycles can effectively trigger monomer polymerization to form a protective layer, resulting in interface stability, excellent cycling performance, and passing all 135°C thermal shock cycles. However, when a thermal initiator is absent in the electrolyte, cycling at 0°C for 190 cycles and at 25°C for 530 cycles fails to polymerize the monomers, resulting in no thermal protection, a significant reduction in cycling performance, and complete ignition during thermal shock, rendering the safety feature completely ineffective.

[0112] Comparing Examples 1, 40-41, and 44-45, it can be seen that when the value of R is in the range of 0.005–0.1, the battery cycle life is 315-335 cycles at 0℃ and 788-825 cycles at 25℃. The polymerization inhibitor dosage is moderate, which can suppress room temperature polymerization, retain thermal response, and achieve optimal balance between battery cycle life and thermal safety. When the value of R is less than 0.005, the battery cycle life is 260 cycles at 0℃ and 680 cycles at 25℃. The polymerization inhibitor is insufficient, and self-polymerization is easy at room temperature, resulting in a decrease in cycle life and a rise in thermal shock temperature to 175℃. When the value of R is greater than 0.1, the battery cycle life is 240 cycles at 0℃ and 630 cycles at 25℃. The polymerization inhibitor is excessive, and normal polymerization cannot be achieved at high temperatures, resulting in protection failure and a deterioration in cycle life. When there is no polymerization inhibitor in the electrolyte, three batteries catch fire during thermal shock, with a center temperature of 182℃, and safety deteriorates sharply.

[0113] Comparing Examples 1, 5-6, 8-9, 24, and Comparative Example 4, it can be seen that when the M / I ratio is 0.2–5.0, after 245-340 cycles at 0℃ and 650-830 cycles at 25℃, the monomer-initiator ratio is matched, polymerization is controllable, the interface is not damaged, and the overall performance is good. When the M / I ratio is 0.5–2.0, after 245-335 cycles at 0℃ and 650-825 cycles at 25℃, the ratio is optimal, the polymer layer is dense and stable, and the cycling and thermal safety are optimal. When the M / I ratio is less than 0.2, after 150 cycles at 0℃ and 450 cycles at 25℃, the monomer content is too low to form a film, thermal shock ignition occurs, and protection fails. When the M / I ratio is greater than 5.0, after 290 cycles at 0℃ and 750 cycles at 25℃, the thermal initiator content is too low, initiation is insufficient, polymerization is incomplete, and both cycling and safety deteriorate.

[0114] Comparing Examples 1, 3, 40-43, and 46, it can be seen that when the (M+I) / R ratio is 10–500, the polymerization system and inhibitor ratio are suitable after 225–338 cycles at 0°C and 610–830 cycles at 25°C, indicating strong controllability and good battery performance. When the (M+I) / R ratio is 40–200, the polymerization system and inhibitor ratio are suitable after 310–338 cycles at 0°C and 780–830 cycles at 25°C. The optimal ratio results in stable polymerization at room temperature and sufficient polymerization at high temperatures, leading to the longest cycle time and the lowest thermal shock temperature. When the (M+I) / R ratio is less than 10, the cycle time is 210 cycles at 0℃ and 580 cycles at 25℃, indicating excessive inhibition of polymerization, making high-temperature polymerization difficult and significantly reducing the cycle time. When the (M+I) / R ratio is greater than 500, the cycle time is 260 cycles at 0℃ and 680 cycles at 25℃, indicating insufficient inhibition of polymerization, self-polymerization at room temperature, poor ion conduction, and decreased cycle time and safety.

[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. An electrolyte, characterized in that: The electrolyte includes a thermally triggered in-situ polymerization additive, which comprises a polymerizable monomer additive and a thermal initiator. Taking the total mass of the electrolyte as 100%, the polymerizable monomer additive accounts for M% of the total mass of the electrolyte, where M ranges from 0.4 to 5. The thermal initiator accounts for I% of the total mass of the electrolyte, where I ranges from 0.5 to 2. The values ​​of M and I satisfy the following conditions: Equation 1: 0.2≤M / I≤5.

0.

2. The electrolyte according to claim 1, characterized in that: The thermally triggered in-situ polymerization additive further includes a polymerization inhibitor, wherein the polymerization inhibitor accounts for R% of the total mass of the electrolyte, and the value of R ranges from 0.005 to 0.1; the M value, the I value, and the R value satisfy the following conditions: Equation 2: 10≤(M+I) / R≤500.

3. The electrolyte according to claim 2, characterized in that: The value of M ranges from 1 to 4; the value of I ranges from 1 to 2; the value of R ranges from 0.01 to 0.05; the values ​​of M, I, and R satisfy the following conditions: Equation 3: 0.5 ≤ M / I ≤ 2.0; Equation 4: 40≤(M+I) / R≤200.

4. The electrolyte according to claim 1, characterized in that: The polymerizable monomer additive includes a C=C functional group and a functional side chain; the C=C functional group includes one or more of CH2=C(R)-COO-, CH2=CH-, CH2=CH-CH2-, or -C≡CH; the functional side chain includes -C n H 2n-1 (1≤n≤6), -O-, -F, -C n F 2n-1 (1≤n≤6), -OC n H 2n - (1≤n≤6), one or more of cyclic carbonates and -CN.

5. The electrolyte according to claim 4, characterized in that: The polymerizable monomer additive includes One or more of the following: trifluoroethyl methacrylate, 1,3-dioxolane-2-one vinyl ether, allyl glycidyl ether, perfluorohexyl ethyl acrylate, and 2-vinyl-1,3-dioxolane.

6. The electrolyte according to claim 1, characterized in that: The thermal initiator includes at least two of a first thermal initiator, a second thermal initiator, and a third thermal initiator, wherein the decomposition temperature of the first thermal initiator is 80-100℃; the decomposition temperature of the second thermal initiator is 100-130℃; and the decomposition temperature of the third thermal initiator is 140-160℃.

7. The electrolyte according to claim 6, characterized in that: The thermal initiator includes a first thermal initiator and a second thermal initiator, wherein the value of I ranges from 0.6 to 1.8; the mass ratio of the first thermal initiator to the second thermal initiator is (1–2):(1–3). Alternatively, the thermal initiator may include the first thermal initiator and the third thermal initiator, wherein the value of I ranges from 0.7 to 2.0; and the mass ratio of the first thermal initiator to the third thermal initiator is (1–2):(1–4). Alternatively, the thermal initiator may include the second thermal initiator and the third thermal initiator, wherein the value of I ranges from 0.5 to 1.6; and the mass ratio of the second thermal initiator to the third thermal initiator is (1–3):(1–2). Alternatively, the thermal initiator may include the first thermal initiator, the second thermal initiator, and the third thermal initiator, wherein the value of I ranges from 0.8 to 2.0; and the mass ratio of the first thermal initiator, the second thermal initiator, and the third thermal initiator is (1–2):(1–3):(0.5–2).

8. The electrolyte according to claim 6, characterized in that: The first thermal initiator includes one or more of azobisisobutyronitrile and azobisisoheptanenitrile; And / or, the second thermal initiator includes one or more of dicumyl peroxide, tert-butyl peroxide (2-ethylhexanoate), and dimethyl azobisisobutyrate; And / or, the third thermal initiator includes one or more of di-tert-butyl peroxide or 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane and 1,3-bis(tert-butylperoxyisopropyl)benzene.

9. The electrolyte according to claim 2, characterized in that: The polymerization inhibitor includes one or more of p-methoxyphenol, tetramethylpiperidine oxide, p-benzoquinone, and 3,5-di-tert-butyl-4-hydroxytoluene.

10. The electrolyte according to claim 1, characterized in that: It also includes lithium salt, non-aqueous organic solvent, and functional additives; with the total mass of the electrolyte as 100%, the lithium salt accounts for 8%–20% of the total mass of the electrolyte; the non-aqueous organic solvent accounts for 75%–90% of the total mass of the electrolyte; and the functional additives account for 0.5%–7% of the total mass of the electrolyte.

11. A battery, characterized in that: It includes a positive electrode, a negative electrode, a separator, and the electrolyte as described in any one of claims 1 to 10.